Primary Productivity of Phytoplankton in The Mandalika Coastal Waters Special Economic Zone, Central Lombok Regency - Fidyantini, Findi; Candri, Dining Aidil; Japa, Lalu; Ghazali, Mursal (Jurnal Biologi Tropis, 2024)
The research entitled "Primary Phytoplankton Productivity in the Mandalika Coastal Waters Special Economic Zone, Central Lombok Regency" was conducted from March to August 2023. This study aims to analyze the primary productivity of phytoplankton, physical and chemical parameters in Mandalika Coastal waters at three different station: station I (Kuta Beach), stasion II (Tanjung Aan), and stasion III (Gerupuk Bay) using dark and light bottles. The research results show that the Mandalika Coastal waters have phytoplankton primary productivity values ranging from 122,619 – 329,166 mgC/m2/day. The lowest productivity value (122,619 mgC/m2/day) occurs at station III these were classified as mesotrophic. Station III has also relatively lower physical and chemical parameter values such as an average pH of 7,7 mg/L and an average temperature of 29ºC compared to other stations. The highest productivity value accured at stasions II and I (329,166 mgC/m2/day and 189,285 mgC/m2/day) both were classified as eutrophic. These were supported by pH worth 7.8 mg/L and temperatures ranging from 29,3 – 29,7 ºC, where the value is relatively higher than in station III.